Coarse-graining the structure of polycyclic aromatic hydrocarbons clusters. Issue 20 (8th April 2016) - Hernández-Rojas, J.; Calvo, F.; Wales, D. J.
Abstract : Clusters of polycyclic aromatic hydrocarbons are essential components of soot and may concentrate a significant fraction of carbon matter in the interstellar medium. Abstract : Clusters of polycyclic aromatic hydrocarbons (PAHs) are essential components of soot and may concentrate a significant fraction of carbon matter in the interstellar medium. In this contribution, coarse-grained potentials are parameterized using all-atom reference data to model PAH molecules, such as coronene (C24 H12 ) or circumcoronene (C54 H18 ), and their aggregates. Low-energy structures of pure coronene or circumcoronene clusters obtained using basin-hopping global optimization are found to agree with atomistic results, and consist of finite 1D columnar motifs, sometimes juxtaposed in larger clusters. The structures are only weakly perturbed when quadrupolar interactions are included. π-Stacking also dominates in binary coronene/circumcoronene aggregates, although intriguing motifs are predicted in which one or more molecules are sandwiched between the other PAH species. The coarse-grained model is also extended to account for interaction with a flat graphitic substrate. In this case, binding is stronger with the substrate than with other molecules, and the PAHs are predicted to arrange into a flat triangular monolayer.